Flow-based approach for holistic factory engineering and design - Constantinescu, C.; Westkämper, E. (НТУ "ХПІ", 2010)
The engineering of future factories requires digital tools along life cycle phases from investment planning to ramp-up. Manufacturers need scientific-based integrated highly dynamic data management systems for the participative and integrated factory planning. The paper presents a new approach for the continuously integrated product design, factory and process planning, through a service-oriented architecture for the implementation of digital factory tools. A first prototype of the digital factory framework has been realised by a comprehensive scenario for factory, equipment and process planning. The phases of factory operation and equipment maintenance are integrated, as well. The enabling technologies, grid computing and workflow management, which supports the comprehensive and integrated engineering of products, factory and processes are shortly introduced.
Keywords: digital factory; workflow management; grid engineering